EVALUASI PELAKSANAAN PROGRAM SKRINING HIPOTIROID KONGENITAL OLEH PUSKESMAS KARANGREJO KOTA METRO, LAMPUNG - Adelia Anggraini; Chriswardani Suryawati; Eka Yunila Fatmasari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Congenital Hypothyroidism (CH) has long been recognized as a cause of mental retardation. Untreated, CH has devastating effects on growth and development of infants. Simply put, CH is inadequate thyroid hormone production in newborn infants. One such effort is the earliest possible detection since newborns or neonatal screening performed in infants aged 48-72 hours. In Indonesia, neonatal screening are not developed yet. Karangrejo Health Center is one of the health facilities performing CH screening in Metro City, Lampung. Nevertheless, the implementation of a neonatal screening program presents many problems. This study aims to evaluate the execution of the Congenital Hypothyroidism Screening Program seen from the input, process, and output variables. This study is a qualitative study using a depth interview method to 13 informants and this study observes on the sub-variables such as facilities and methods. The result of the study on the input variable shows that there is enough availability of human resource but not enough facilities and funds to cover the necessities such as filter papers kit, and there is no SOP. Process variable shows that activity of socialization and education of SHK is not effectively done because the lack of participation of audience. Output variable indicates that program coverage is low, within 141 newborn, 35 newborn are tested in 2017 and 13 newborn until April 2018. To advance the CH screening program, the suggestion given is DHO expetcted to fix and improve the infrastructure planning, also monitoring and evaluation function have to be done properly. It is necessary for the health center to increase the coordination and the communication for all the organizer cadres, DHO, and cross sectors for the continuity of the execution Congenital Hypothyroidism Screening Program activities and make standard operating procedures. People can participate in having the CH Screening Program since CH can affects the growth and development of children and also affects the quality of human resources in the future.